2019
DOI: 10.1167/iovs.18-25247
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure in General and Diabetic Populations From Southern China: the Dongguan Eye Study

Abstract: PURPOSE. To investigate the distribution and risk factors for intraocular pressure (IOP) among general and diabetic populations in Southern China. METHODS. The study participants aged 40 years or older were enrolled from the Dongguan Eye Study, a population-based cross-sectional study from September 2011 to February 2012. Systemic and ophthalmic examinations were performed, and diabetes status was screened based on the American Diabetes Association diagnostic criteria (2010). IOP was measured by a noncontact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…A retrospective, population-based study by Kim et al involving 80 glaucoma patients and 4015 controls did show that low HDL-C was significantly associated with POAG with normal baseline IOP (OR = 0.96, 95% CI, 0.94-0.99; p = 0.004) [84]. A recent cross-sectional study revealed that higher IOP was significantly associated with lower HDL-C (mean IOP difference between low and high HDL-C group = −0.68; 95% CI, −0.99 to −0.36; p <0.001) [85]. However, on the other hand, a cross-sectional study in a Japanese population reported that an increase in serum HDL-C by 1 mmol/L was significantly associated with a +0.42 mm Hg IOP change (95% CI = 0.35-0.49, p < 0.0001) [86].…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…A retrospective, population-based study by Kim et al involving 80 glaucoma patients and 4015 controls did show that low HDL-C was significantly associated with POAG with normal baseline IOP (OR = 0.96, 95% CI, 0.94-0.99; p = 0.004) [84]. A recent cross-sectional study revealed that higher IOP was significantly associated with lower HDL-C (mean IOP difference between low and high HDL-C group = −0.68; 95% CI, −0.99 to −0.36; p <0.001) [85]. However, on the other hand, a cross-sectional study in a Japanese population reported that an increase in serum HDL-C by 1 mmol/L was significantly associated with a +0.42 mm Hg IOP change (95% CI = 0.35-0.49, p < 0.0001) [86].…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…The incidence was 1.4% from another study performed in a French cohort 16 . It was estimated that 7% of the adults aged 40 years and older in China had increased IOP 17 . The incidence of glaucoma was 3.5% among the population from 40 to 80 years old in a global study performed in 2013 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The design and baseline characteristics of DES in detail were published previously. 21–23 In brief, residents aged 40 years or older from Hengli Town of Dongguan were recruited from September 2011 to February 2012. A total of 11 357 participants were eligible for inclusion and 8952 (78.8% of eligible) participants were successfully enrolled for systemic and ophthalmic examinations.…”
Section: Methodsmentioning
confidence: 99%